2014
DOI: 10.2147/ijn.s57048
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of BSA-loaded microspheres based on multi-(amino acid) copolymer for protein delivery

Abstract: A multi-(amino acid) copolymer (MAC) based on ω-aminocaproic acid, γ-aminobutyric acid, L-alanine, L-lysine, L-glutamate, and hydroxyproline was synthetized, and MAC microspheres encapsulating bovine serum albumin (BSA) were prepared by a double-emulsion solvent extraction method. The experimental results show that various preparation parameters including surfactant ratio of Tween 80 to Span 80, surfactant concentration, benzyl alcohol in the external water phase, and polymer concentration had obvious effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…In this review, silk fibroin [ 11 ], keratin [ 12 ], collagen [ 13 ], gelatin [ 14 ], elastin [ 15 ], corn zein [ 16 ], and soy protein [ 17 ] will be given particular attention due to their popularity in biomaterials research ( Figure 1 ). However, additional protein polymers such as casein [ 18 ], fibrinogen [ 18 ], hemoglobin [ 19 ], bovine serum albumin [ 20 ], gluten [ 20 ] have also been used to create nanoparticles.…”
Section: Categories Of Protein Materialsmentioning
confidence: 99%
“…In this review, silk fibroin [ 11 ], keratin [ 12 ], collagen [ 13 ], gelatin [ 14 ], elastin [ 15 ], corn zein [ 16 ], and soy protein [ 17 ] will be given particular attention due to their popularity in biomaterials research ( Figure 1 ). However, additional protein polymers such as casein [ 18 ], fibrinogen [ 18 ], hemoglobin [ 19 ], bovine serum albumin [ 20 ], gluten [ 20 ] have also been used to create nanoparticles.…”
Section: Categories Of Protein Materialsmentioning
confidence: 99%
“…In addition, in the gastrointestinal tract a decrease in the pH value of the adjacent microenvironment may induce side effects such as infl ammation. [33][34][35] Hence, it is essential to explore new biomaterials with versatile encapsulation strategies to meet the ever increasing demand for encapsulating biomaterials.…”
Section: Macromolecular Encapsulation and Characterization Of Naturalmentioning
confidence: 99%
“…A previous study verified that the biostructure of this scaffold was very similar to natural human bone with both porosity and perfect biodegradability, which should make it possible for the scaffold to become an ideal antibiotics carrier for the repair of infected bony defects. [ 1 ] Although it was theoretically demonstrated that all of the scaffold monomers and degradation products had no significant toxicity or side effects to the human body,[ 2 3 ] the scaffold would undergo changes and reactions during procedures including fabrication, storage, and sterilization. Furthermore, the blood concentration of the loaded antibiotics could reach toxic levels at certain times, especially in the early stages after implantation.…”
Section: Introductionmentioning
confidence: 99%